2018
DOI: 10.1128/aem.01517-17
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Heterotrophic Bacterial Assemblages within Synechococcus Cultures

Abstract: Interactions between photoautotrophic and heterotrophic microorganisms are central to the marine microbial ecosystem. Lab cultures of one of the dominant marine photoautotrophs, , have historically been difficult to render axenic, presumably because these bacteria depend upon other organisms to grow under these conditions. These tight associations between and heterotrophic bacteria represent a good relevant system to study interspecies interactions. Ten individual strains, isolated from eutrophic and oligotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
76
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 107 publications
1
76
3
Order By: Relevance
“…Near‐surface water samples (27.6°C) were collected from the South China Sea near Yongxing Island (~17° N, ~112° E) in April 2018 for incubation inocula. The sea water in this area is oligotrophic, with PO 4 3− and NO 3 − concentrations below 0.1 ÎŒM (Zheng et al ., ). Seawater was pre‐filtered with a 20‐Όm pore size filter to remove eukaryotic cells, and then maintained in the dark for three days prior to DOM addition experiments.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Near‐surface water samples (27.6°C) were collected from the South China Sea near Yongxing Island (~17° N, ~112° E) in April 2018 for incubation inocula. The sea water in this area is oligotrophic, with PO 4 3− and NO 3 − concentrations below 0.1 ÎŒM (Zheng et al ., ). Seawater was pre‐filtered with a 20‐Όm pore size filter to remove eukaryotic cells, and then maintained in the dark for three days prior to DOM addition experiments.…”
Section: Methodsmentioning
confidence: 97%
“…The isolate Synechococcus sp. YX04‐3 was obtained from ocean waters near Yongxing Island in the South China Sea (Zheng et al ., ), which was also the location of the subsequent DOM addition experiments. Synechococcus cells grown to exponential phase were collected by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…The lifestyles and genomic characteristics of dominant heterotrophic bacteria associated with coastal Synechococcus sp. strain XM-24 cultures have been investigated in detail, but the associated heterotrophs also show geographic distribution patterns that are related to the environments of Synechococcus strain isolation (25,26). Thus, several important aspects of these relationships remain unclear including (i) how open ocean Synechococcus culture ecotypes interact with their associated heterotrophic bacteria, (ii) how different heterotrophic bacterial populations interact with single cyanobacterial strains in coculture systems, and (iii) the nature of the roles of major bacterial populations in the Synechococcus culture systems.…”
mentioning
confidence: 99%
“…Recently, Zheng et al . (), observed a geographical pattern of heterotrophic bacteria associated with different marine Synechococcus strains, indicating that strains living in the same area tend to be associated with similar communities. It remains, however, unclear whether the Synechococcus genotype or the environment is the main drivers of Synechococcus interactions with the surrounding microbial community.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies have shown that different Synechococcus strains could co-exist in the same site but respond differently to environmental changes, suggesting niche partitioning (Ferris et al, 2003;Allewalt et al, 2006;Becker et al, 2007;Becraft et al, 2011;Callieri et al, 2012). Recently, Zheng et al (2018), observed a geographical pattern of heterotrophic bacteria associated with different marine…”
Section: Introductionmentioning
confidence: 99%